Neglect testing at your peril. - O'Connor, P.D.T (IEEE spectrum)
In developing products and systems, testing, and not design, is usually the more expensive, time-consuming, and difficult activity. Done correctly, development testing involves multidisciplinary teamwork from engineers proficient in design, development, manufacture, and maintenance. Testing ensures that the design meets performance, safety, durability, and reliability requirements, not to mention statutory demands, and should ensure that the product continues to meet them once in use. Engineering organizations must develop a philosophical foundation for all that relates to the testing of their products and systems. Intrinsic to this philosophy should be the maxim that effective testing is a value-adding process, not a cost. The design engineer might feel there is no need for extensive testing, the project engineer might feel otherwise. The finance people will want to minimize cost and, therefore, the amount of testing. If all can agree on a philosophy that takes account of what is known and what is uncertain, and of the other essential factors, such as costs, timing, markets, regulations, and safety, then at least there will be a foundation for rational planning and decision-making